Hierarchical Model Rule Based Nlp for Semantic Training Representation Using Multi Level Structures - Liu, Fangmian; Bian, Qiyuan (Informatica, 2024)
During evaluation of large amounts of natural language texts, the utilisation of multi-level models is essential for the purpose of extracting knowledge that is relevant. It is essential to complete these duties to solve a variety of concerns relating to the development of textual information as well as its analysis. It is necessary to have a substantial quantity of annotated texts that contain various levels of lexical, syntactical, semantic, and narrative information to develop multi-level models for natural language texts. due syntactical annotations are maintained in a tree structure, these annotated texts are frequently referred to as text corpora or treebanks. This is due of the tree structure. Semantic treebanks are a relatively new development in this area that were introduced not too long ago. These treebanks join syntactical trees through logically-expressed smart representations of phrase sense. During the last few years, a great number of semantic treebanks that contain superficial as well as deep semantic information have been constructed. There have been a lot of different ways created, both manually and mechanically, for generating semantic treebanks. Because there aren't many standards that are universally accepted in this quickly developing subject, many semantic banks include vastly varied kinds of information. This is especially true on the lexical level. The authors of this work investigate a variety of semantic treebanks and the ways in which such treebanks could be used for text modelling. They investigate the various kinds of information, such as semantic, narrative, syntactical, and lexical data, that are stored in these treebanks. The authors also study the quantity and character of relevant corpora in addition to the key tools utilised for working with the data included within treebanks. These methods have a wide range of applications in decision-making processes that are concerned with the generation and analysis of text. An example of their usage is for annotating and retrieving information resources to facilitate collaborative development of a domain information space based on ontology, particularly in scientific research and learning. Additionally, you can use them to create and re-write texts for a variety of purposes, including fiction writing, marketing, and scientific communication.